EVALUASI PELAKSANAAN SISTEM VERIFIKASI DI KANTOR (VEDIKA) BPJS KESEHATAN DI RUMAH SAKIT UMUM WILLIAM BOOTH SEMARANG - Elsa Febrie Alvianitasari; Sutopo Patria Jati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Acceleration of claims verification becomes important in creating an effective and efficient health services. As a result, BPJS Kesehatan takes the solution to change manual claim verification system to electronic claim verification system to facilitate health providers, but it takes a transition period, called vedika (verifikasi di kantor) BPJS Kesehatan. 10 out of 24 hospital in Semarang have implemented vedika system as of December 2017, and William Booth Semarang General Hospital is the first hospital selected BPJS Kesehatan to implement Vedika system. The purpose of the study is to evaluate implemented vedika system BPJS Kesehatan in William Booth Semarang General Hospital. The study uses qualitative methods through in-depth interviews with key informants casemix section and informant triangulation section of casemix and head of PMR BPJS Kesehatan. Variables of the research are human resources, procedures, facilities and infrastructure, planning, organizing, implementation, assessment, and output. The result of the research is implemented vedika system by the hospital has not been effective because there is the return of claim file and the late of claim payment. It is because of the doctor's writing is less clear, the limitations of officers, there is no monitoring and evaluation of the implementation of the vedika system. The doctor's writing is result in errors coding and pending claims. The limitation of officers with incremental cases each month result in late claims submission so claim payments are lat. The absence of monitoring and evaluation resulted in the same error being repeated. Then the claim is said to succeed if the claim is paid, on time and 100%. The suggestions are holding on training on capacity building of officers and adding officers